2017
DOI: 10.1002/joc.5196
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variability in absolute indices of temperature extremes over Nigeria: linkage with NAO

Abstract: The present study examines trends in extreme temperature absolute indices [warmest day (TXx), coldest day (TXn), warmest night (TNx) and coldest night (TNn)] using the newly homogenized daily minimum and maximum temperature series from 21 stations in Nigeria for the period 1971-2012. The indices provide an understanding of the characteristics of changing temperature, in light of the present anthropogenic global warming. Trends in the indices and the statistical significance are obtained using the modified Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
1
15
1
Order By: Relevance
“…The only nationwide study of climate extremes in Nigeria is that recently carried out by Abatan et al (, ). Abatan et al () used daily station temperature data from 1971 to 2012 with focus on percentile‐based temperature extreme indices to show that there is a significant increase in the fraction of hot extremes and a decrease in the fraction of cold extremes at seasonal and annual timescales.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only nationwide study of climate extremes in Nigeria is that recently carried out by Abatan et al (, ). Abatan et al () used daily station temperature data from 1971 to 2012 with focus on percentile‐based temperature extreme indices to show that there is a significant increase in the fraction of hot extremes and a decrease in the fraction of cold extremes at seasonal and annual timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Abatan et al () used daily station temperature data from 1971 to 2012 with focus on percentile‐based temperature extreme indices to show that there is a significant increase in the fraction of hot extremes and a decrease in the fraction of cold extremes at seasonal and annual timescales. On the other hand, Abatan et al () used both an observed and an ERA‐20C gridded temperature data set to study trends in absolute temperature extreme indices from 1971 to 2012. Their analysis showed that the frequency and intensity of extreme temperature events over Nigeria are more pronounced during the dry season months (November–February).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of droughts involves numerous interacting climate processes and various land-atmosphere feedbacks [85]. In particular, the vertical velocity (also represented by omega) has usually been used for drought assessment [86,87]. A vertical cross-section of the mean values and anomalies of omega for the peak month of the most severe drought episodes that affected each climate sub-region between 1980 and 2017 is shown in the top and bottom panels of Figure 8, respectively.…”
Section: Characteristics Of the Most Severe Meteorological Drought Epmentioning
confidence: 99%